Lei de Wagner, ilusao fiscal e causalidade entre receitas e despesas : uma análise das finanças públicas brasileiras - Prado, Pedro Henrique Martins (2017)
The aim of this research is to analyze the Brazilian government expenditure dynamics for the period 1997-2013. The analysis is based on three approaches: Wagner's Law, Fiscal Illusion, and the Revenue and Expenditure Nexus. As shown in the theoretical revision, the majority of public spending is determined by rigid rules, but there can be di erences associated to the determinants of distinct types of spending. The results related to the estimations of ARDL Models (Bounds-Testing Approach to Cointegration) show that: i) a positive relationship between real minimum wage and public spending; ii) irrelevance of in ation tax on government nancing; iii) Fiscal Illusion, probably due to indirect taxes; iv) validity of Wagner's Law only for autonomous spending; v) causality between tax and spend depending on how the public spending is broken down.